Answer:
Step-by-step explanation:
Theres no photo
Answer:
The value of n is -6
Step-by-step explanation:
- If the function f(x) is translated k units up, then its image is g(x) = f(x) + k
- If the function f(x) is translated k units down, then its image is g(x) = f(x) - k
- The vertex form of the quadratic function is f(x) = a(x - h)² + k, where a is the coefficient of x² and (h, k) is the vertex
∵ k(x) = x²
→ Its graph is a parabola with vertex (0, 0)
∴ The vertex of the prabola which represents it is (0, 0)
∵ The given graph is the graph of p(x)
∵ Its vertex is (0, -6)
∴ h = 0 and k = -6
∵ a = 1
→ Substitute them in the form above
∴ p(x) = 1(x - 0)² + -6
∴ p(x) = x² - 6
→ Substitute x² by k(x)
∴ p(x) = k(x) - 6
∵ p(x) = k(x) + n
→ By comparing the two right sides
∴ n = -6
∴ The value of n is -6
Look at the attached figure for more understanding
The red parabola represents k(x)
The blue parabola represents p(x)
Answer:
For the first one its: Volume = 402.12in³
For the second one its: Volume = 201.0619 in³
Step-by-step explanation:
For the first one work:
Volume = 3.1416 x 42 x 8
= 3.1416 x 16 x 8
For the second one work:
Volume = 3.1416 x 42 x 4
= 3.1416 x 16 x 4
6 months goes into 2 years 4 times
30 x 4 = 120
120% of 15,000 is
100% is 1,500
10% is 150
150 x 2 = 300 (20%)
1,500+300=1,800
15,000+1,800=16,800
hope this helped
Answer:
See below
Step-by-step explanation:
<u>Parent function:</u>
<u>Transformed function:</u>
- y = 4(3)⁻²ˣ⁺⁸ + 6, (note. I see this as 8, sorry if different but it doesn't make any change to transformation method)
<u>Transformations to be applied:</u>
- f(x) → f(-x) reflection over y-axis
- f(-x) → f(-2x) stretch horizontally by a factor of 2
- f(-2x) → f(-2x + 8) translate 8 units right
- f(-2x + 8) → 4f(-2x + 8) stretch vertically by a factor of 4
- 4f(-2x + 8) → 4f(-2x + 8) + 6 translate 6 units up